Birth Weight/ Placental Weight Ratios: Does the association differ between early- and late-onset preeclampsia? - Podjanee Phadungkiatwattana; Songphol Puttasiri (The Royal Thai College of Obstetricians and Gynaecologists, 2019)
Objective: Early- and late-onset preeclampsia (PE) may differ in pathophysiology and this can be reflected in differences in birth weight/placental weight (BW/Pl) ratios. Therefore, we compared BW/Pl ratios of births with early- and those with late-onset PE. Materials and Methods: The retrospective descriptive study included all hospital-based singleton births of 24-43 weeks' gestation between January 2007 and December 2016. A total of 51,940 pregnant women were divided into three groups: early-onset PE, late-onset PE, and pregnant women without PE. Birth weight/placental weight were compared among 3 groups. Results: The mean (± standard deviation; SD) BW/Pl ratios were significantly different in early-onset PE and late-onset PE compared with the control group (3.91 + 0.93 in early-onset PE, 4.85 + 0.91 in late-onset PE and 5.17 + 0.90 in the control group, p < 0.001). The factors significantly associated with BW/Pl ratios were race, infant gender, diabetes mellitus (DM), gestational age at delivery, early-onset PE, late-onset PE, small for gestational age (SGA) and large for gestational age (LGA). After adjustment for DM, gestational age at delivery, late-onset PE, SGA and LGA, the BW/Pl ratio was still associated significantly more with early-onset PE than with late-onset PE. Conclusion: The BW/Pl ratios of preeclamptic women differed between early- and late-onset PE, and that early-onset PE may be commonly associated with placental efficiency. This suggests that preeclampsia consists of several different processes manifesting as a single disease.